Evaluation of Apolipoprotein Profile in Hiv/Aids Subjects in Pre and Post 12 Months Antiretroviral Therapy Using 1.5 Mg/Ml Troponin Diagnostic Cut-Off for Myocardial Infarction in Nauth Nnewi, South Eastern Nigeria - Ezeugwunne, Ifeoma Priscilla; Onyenekwe, Chinedu Charles; Ahaneku, Joseph Eberendu; Aikpitanyi–Iduitua, Godwin Aigbedo; Ibemere, Obinna David; Samuel, Ike Ifeanyichukwu; Oguaka, Victor Nwabunwanne; Onyedikachukwu, Amaifeobu Clement (British Journal of Healthcare and Medical Research, 2022)
Patients infected with HIV have an increased risk of developing heart disease. HIV causes Acquired Immune Deficiency Syndrome AIDS by invading the host cells and depleting the immune system. It has been reported that acute myocardial infarction might occur at 1.5 ng/ml troponin level. Information on cardiac status in HIV infected subjects in Nigeria is scanty. The aim is to evaluate the serum apolipoproteins in HIV subjects, in pre- and post- 12 months antiretroviral therapy (ART) using 1.5ng/ml troponin diagnostic cut-off for myocardial infarction. A total of 100 HIV subjects not on ART devoid of malaria co-infection were recruited in this study. Apolipoprotein parameters were re-classified based on 1.5 ng/ml troponin diagnostic cut-off for myocardial infection. 30 out of the 100 participants that were within 1.5 ng/ml troponin diagnostic cut-off for myocardial infection were followed up on commencement of ART for 12 months. Their blood samples were drawn at 3, 6, 9 and 12 months for some apolipoproteins and CD4 analyses using standard laboratory methods. The results showed that as months of antiretroviral therapy deepened or lengthened, the numbers of HIV positive subjects with values higher than the troponin diagnostic value reduces when compared with values before therapy (p<0.05). Paired-wise comparison showed that there were significantly higher levels of CD4 counts, Apo A2, Apo C2, Apo E but lower levels ApoA1, Apo B and Apo C3 in symptomatic HIV individuals before ART when compared with values after therapy at p<0.05 respectively. These lower levels ApoA1, Apo B and Apo C3 in symptomatic HIV individuals after therapy may indicate possible cardio- protective effect of the drug on the heart, which may connote immune recovery. The troponin values were significantly higher than the diagnostic cut off for acute myocardial infarction (AMI) studied amongst the group at p<0.05 respectively. This may imply that AMI may occur at any group of study.